Reduced Number of acute myocardial infarction cases at the time of lockdown during the COVID-19 pandemic in northern Iraq-Erbil: In search for exploring the possible explanation behind it - Shwan Othman Amen; Banan Qasim Rasool (Medical Journal of Babylon, 2021)
Background: Coronavirus disease-2019 (COVID-19) pandemic has led to a radical transformation of economic, social, and health-care networks. COVID-19 pandemic has reported a substantial drop in the number of patients presenting to cardiology Emergency Departments with acute coronary syndromes/acute myocardial infarction (ACS/AMI) and a drop in number of cardiac procedures. Objective: The objective was to describe how lockdown and COVID-19 pandemic has affected the evolution of AMI and hospital admissions due to ACS. We aimed to assess the impacts of COVID-19 on cardiology services and procedures performed on a daily basis before and during the pandemic. Materials and Methods: This single-centered retrospective study included all the consecutive patients with ACS/AMI including ST-segment elevation myocardial infarction (STEMI) and non-STEMI admitted to ER of Surgical Specialty Hospital-Cardiac Center/Erbil-Iraq, from the start of the lockdown (March 15, to April 15, 2020). The same analysis was conducted among patients presenting with ACS/AMI at the same identical time period before Lockdown (March 15, to April 15, 2019). Results: A total number of 40 patients admitted at SSH/Cardiac Center-Erbil with ACS/AMI during the study period, and showed a 37.5% drop in the number of patients with Myocardial Infarction comparing with the corresponding time window before the COVID-19 pandemic. Conclusion: These preliminary results strongly demonstrate a decrease in the number of admissions for ACS/AMI during the lockdown period (March 15, to April 15, 2020) due to multiple reasons.